HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP DENGAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA DI UNIT KERJA PRODUKSI PENGECORAN LOGAM - Saputro, Vondra Anggi, Heru Subaris Kasjono., SKM., M.Kes, Dr. Suwaji, M.Kes (2015)
Personal protective equipment is a set of tools used to protect the safety of the whole or in part of the body from the potential danger of accidents and occupational diseases. The use of appropriate personal protective equipment can reduce the rate of accidents. The purpose of this study was to determine the relationship between knowledge and attitudes to the use of Personal Protective Equipment (PPE) for workers at a metal foundry production unit. This research uses Analytical observational method with cross sectional approach. The research was conducted at CV. Manunggal Steel Prosperous Hamlet Batur Village Tegalrejo Ceper District of Klaten regency. The population in this study, workers in metal casting production unit. The sample in this study as many as 40 people. The sampling using Total Sampling technique while using the techniques of statistical test Chi Square test. The results showed the respondents knowledge is not good (52.5%) and negative attitude of the respondents (55.0%). Statistical analysis showed that there is a relationship between knowledge (p= 0.002) and attitude (p= 0.005) with the use of personal protective equipment for workers at a metal foundry production unit.